Social media, digital literacy, and career competence: a mixed methods study among university students in China - Jian, Chen; Zou, Danting; Mahadi, Nomahaza (Frontiers in Psychology, 2025)
IntroductionThe widespread use of social media has transformed how university students develop knowledge and prepare for future careers. However, limited evidence exists on whether structured and purposeful engagement with these platforms can strengthen students’ digital literacy and career competence, particularly within the Asian higher education context.MethodsGuided by Social Cognitive Career Theory and gamified learning principles, this study employed a convergent parallel mixed-methods design. A one-month intervention was implemented with 44 undergraduates from three Chinese universities, involving structured social media tasks delivered through gaming and livestream activities.ResultsQuantitative analyses revealed significant gains in digital literacy, professional skills, learning attitudes, and career competence. Digital literacy also emerged as a strong predictor of both professional skills and career competence. Complementary qualitative findings highlighted students’ enhanced self-regulation, stronger employability orientation, and a shift toward viewing social media as a professional rather than purely social tool.DiscussionThese findings suggest that short, gamified social media interventions can effectively and sustainably enhance students’ digital capabilities and career readiness. The study extends the application of Social Cognitive Career Theory to media-rich learning environments and provides practical implications for higher education institutions seeking to strengthen graduate employability.